Variaciones geomorfológicas en los últimos 50 años de la Isla Damas, Quepos, Costa Rica - Lizano Rodríguez, Omar Gerardo (2001)
Fifthy years of geomorphologic change in Damas Island, Quepos, Costa Rica, were studied from a photographic record that is available since 1947. Coastal dynamics were accelerated by the El Niño Phenomenon in 1997 which was simultaneous with the August-September astronomical tide, one of the highest in the 4-5 year cycle. Additionally, waves with high energy were present in some periods of these months. Processes were enough to break the island in two blocks and to initialize erosion and transport sediment that continues to date. The frequency of tropical storms and the wave energy will be greater in the next years increasing sediment instability processes in parts of the island. Two topographic profiles have shown that the island is not in equilibrium and that adding all the possible mareographic components it will be prone to continued erosion. The marine habitats around the island should be changing because the fresh and salt water input has been modified, specially because alteration in the Parrita and Paquita hydrological river basins, and its effects on the sediments of this system.